Impact of SGLT2 Inhibitor Therapy on Patients Undergoing Cardiac Surgery - Taghiyev, Zulfugar T.; Beier, Lili-Marie; Leweling, Carina; Gunkel, Sophia; Sadowski, Kevin Mike; Assmus, Birgit; Boening, Andreas (The Thoracic and Cardiovascular Surgeon, 2025)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors (SGLT2i) are nephroprotective in patients with recompensated acute and chronic heart failure (HF) and chronic kidney disease, but their potential influence during cardiac surgery is unclear. Currently, discontinuation of SGLT2i at least 2 days before surgery is recommended.Between March 2022 and December 2023, 53 cardiac surgical patients on SGLT2i therapy in addition to standard medical treatment for HF were compared with 447 other HF patients from the same period. After 1:1 covariate adjustment, 33 patients with SGLT2i treatment were matched with 33 controls. The primary endpoint was a change in estimated glomerular filtration rate (eGFR) 36 hours after surgery. Secondary endpoints were changes in eGFR, cumulative urine output, diuretic efficacy, and albuminuria over seven postoperative days.Mean baseline eGFR was similar between the groups (p = 0.973). Thirty-six hours postoperatively, eGFR was significantly higher in the SGLT2i group by a mean difference (MD) of 11.8 mL/min (95% CI [3.12–20.44]; p = 0.009) compared with the control group. The mean urinary albumin level was 18.1 mg/mL lower in the SGLT2i group (95% CI [−42.5–6.33]; p = 0.143). There were numerically positive changes in urine output and diuretic efficacy in the SGLT2i group without significant difference: MD 131.4 mL/24 hours (95% CI [−366.7–629.5]; p = 0.600) and MD 11.3 mL/mg (95% CI [−12.2–34.7]; p = 0.301), respectively, although the dosage of diuretics was higher in controls (30.6 ± 43.7 vs. 51.3 ± 130.1 mg/24 hours; p = 0.268, respectively).SGLT2i may have nephroprotective effects in patients undergoing heart surgery with extracorporeal circulation. More evidence is needed to determine whether SGTL2i needs to be discontinued before surgery.
Keywords: SGLT2i; renal failure; kidney injury; cardiac surgery